A Study of Laboratory Comminution Techniques for Respirable Coal Dust Generation and their Contamination Effects - Jianliang Li; Jan M. Mutmansky (Society for Mining, Metallurgy & Exploration, 1992)
This study analyzed laboratory comminution techniques for respirable mine dust generation and the properties of the resulting dusts. It was the objective of the study to determine the suitability of the resulting dusts in reflecting the properties of natural airborne dust. This paper deals specifically with the amount of contamination introduced into the generated dust as a result of abrasion when using nine different grinding methods. The analysis was made by comparing the content of 25 chemical elements in the lab-generated dusts with the same elements in the airborne coal mine dusts. It was found that all the lab-generated dusts possessed contamination but that several methods produced smaller percentages of contamination and that the residence time in the grinding device was an important factor in the contamination levels.